Digestibilidade, cinética e morfologia digestiva em borregas Santa Inês submetidas a dois planos alimentares - Luigi Francis Lima Cavalcanti (2011)
Thirty six Santa Ines female lambs were distributed on a completely randomized design with a 2x3 factorial arrangement composed of two nutritional planes (ad libitum or restrict) and three slaughter weights (20, 30 or 40 kg). The animals were allocated in metabolic cages with feed, minerals and water bunkers to realize the assays of intake, apparent digestibility and digestive kinetics. To this last assay, was utilized the chromium-mordanted fiber technique in pulse dose, been adjusted the Dhanoa et al. (1980) model to the data obtained for chromium fecal concentration over the 13 sample times after administration (0,5,8,11,14,17,20,23,26,35,47,71 and 96 hours). After these assays, the animals were slaughtered and the viscera and intracavitary adipose tissue were weighed. Samples of ruminal epithelium were collected to do morphological evaluation of ruminal papillae from ventral and cranial sacs. The restriction reduced the intake of all nutrients, although, between slaughter weights, only the animals with 40 kg consumed more nutrients. The dry matter digestibility was different for all weights between ad libitum animals. The restricted diet increased the fiber digestibility and the animals from this group showed higher digesta retention time in the gastrointestinal tract. The carcass yield of lighter animals was lower. The intracavitary fat deposits in ad libitum animals increased following the body weight growth, but the same did not occurred for restricted animals. The rumen-reticular volume was higher in restricted animals, but height and papillae area were smaller for these animals. The absorptive area per square centimeter was higher in animals with intermediary slaughter weight. The liver was markedly affected by slaughter weight and nutritional plane. Nutritional plane and growth were determinant factors in animal nutrition.